Spatial and biomass structure of shallow‐water cape hake (Merluccius capensis) in the light of episodic environmental shifts. (28th June 2022) - Bahamon, Nixon; Kathena, Johannes N.; van der Plas, Anja K.; Kainge, Paulus; Paramo, Jorge; Gordoa, Ana
Abstract: The spatial distribution patterns of Merluccius capensis in the Namibian waters were investigated and related to average environmental conditions during 1996–2020. Fisheries‐independent data and simultaneously collected water temperature and dissolved oxygen data were used from austral summer surveys. A geostatistical kriging approach was employed to evaluate the spatial structure of hakes. Links to environmental conditions were explored via data‐driven generalized additive models (GAMs). M. capensis generally exhibited average patch sizes between 40 and 50 nm at depths between 180 and 280 m. During the extreme episodic water warming in 2011 related to a Benguela‐Niño, the hake patches shrank up to a historical minimum of about 13 nm and moved offshore showing maximum densities at unusual deeper bottoms between 260 and 320 m. The deepening and size reduction of aggregations did not alter the biomass estimates (570 kt) that remained within historical ranges (249–811 kt). Although other extremely warm and cold summers were reported during the study period, no significant impact on the M. capensis patch size was detected. Maximum M. capensis densities were linked to optimal bottom temperature range between 10.1 and 11.8°C, dissolved oxygen values close to zero nearshore, and between 0.8 and 1.4 ml/L offshore. Potential changes of biomass produced by extreme environmental events remained undetected within the interannual biomass ranges, suggesting a high resilience capacity to episodic extreme environmental events.